Diagnosis and evaluation of criteria for conducting surgical treatment in women with cystocele and stress urinary incontinence - О. O. Lyulko; O. O. Burnaz; I. N. Nikitiuk; О. S. Sagan; M. V. Varvashehia (Сучасні медичні технології)
Purpose of the study. Clarification of absolute and relative criteria for the surgical treatment of pelvic pelvic prolapse (PMT) and stress urinary incontinence (SNA).